SUCCESSFUL TREATMENT OF A RECIPIENT WITH MASSIVE THROMBOSIS OF HEART TRANSPLANT LEFT CHAMBERS DURING EXTRACORPOREAL MEMBRANE OXYGENATION - V. N. Poptsov; V. M. Zakharevich; E. A. Spirina; A. M. Golts; S. G. Ukhrenkov; T. A. Khalilulin; E. Z. Aliev (Вестник трансплантологии и искусственных органов)
We present a case report of a 16-year-old man with venoarterial extracorporeal membrane oxygenation (VA-ECMO) for primary graft failure after orthotopic heart transplantation who developed left atrium and left ventricular thrombosis despite systemic anticoagulation. The surgical thrombectomy was performed and the patient was successfully weaned off the extracorporeal support on the first day thereafter.